Cephalometric evaluation of facial soft tisssue in 16-21 years old students with normal occlusion in Kerman - BA Ramazanzadeh; MH Karimi; s Tahmasbi (Isfahan University of Medical Sciences, 2009)
Introduction: The aim of the present study was to cephalometric evaluation of facial soft tissue facial profile for 16-21 years old students of Kerman with normal occlusion.Methods and Materials: In this cross-sectional study, we utilized 59 lateral cephalometric radiographs of 30 girls and 29 boys with mean age of 17.1 years and normal occlusion from Kerman department of orthodontics. Four angular and 10 linear measurements from Holdaway, Ricketts and Subtenly analyses were used to evaluate soft tissue profile. Mean values were utilized to compare girls and boys with each other and with similar studies by t-test using SPSS 12 (α = 0.05).Results: In comparison of girls with boys, soft tissue facial angle, no to H-line and upper lip to E-line were significantly increased in Kermanian girls compared with Kermanian boys; while in boys, upper lip thickness and inferior sulcus to H-line were larger (p<0.05).When comparing with Holdaway soft tissue norms,6 values in boys and 5 values in girls were significantly different. In addition, position of lips and facial convexity showed significant difference with Ricketts and Subtenly norms.Conclusion: Kermanian boys differ from Kermanian girls in an increased lip thickness and more retruded position of chin. In comparison with Holdaway norms, Kermanians have more convex face and thicker chin. Key words: Lateral cephalometry, facial soft tissue, normal occlusion